Oncerochara bolitocharoides gen. et sp. nov., of the tribe Homalotini (Coleoptera: Staphylinidae: Aleocharinae) from Japan - Hashizume, Takuto; Maruyama, Munetoshi (Zootaxa, 2026)
A highly distinctive member of the tribe Homalotini (Coleoptera: Staphylinidae: Aleocharinae) is described from Honshu, Japan, as a new genus and species, Oncerochara bolitocharoides Hashizume & Maruyama, gen. et sp. nov. This taxon is similar to the members of the genus Bolitochara Mannerheim, 1830, but can be clearly distinguished by a broad maxillary galea and clearly transverse pronotum. In particular, the shape of the galea is highly distinctive within the subtribe and may indicate a specialized adaptation for feeding. The species is known from only two specimens. This discovery highlights the hidden diversity of Japanese Aleocharinae and underscores the importance of investigating overlooked ecological niches to fully understand aleocharine biodiversity.